Circadian rhythms in the Drosophila eye may regulate adaptation of vision to light intensity - Nolan, Richard Brent; Fan, Jin-Yuan; Price, Jeffrey L. (Frontiers in Neuroscience, 2024)
The sensitivity of the eye at night would lead to complete saturation of the eye during the day. Therefore, the sensitivity of the eye must be down-regulated during the day to maintain visual acuity. In the Drosophila eye, the opening of TRP and TRPL channels leads to an influx of Ca ++ that triggers down-regulation of further responses to light, including the movement of the TRPL channel and Galpha proteins out of signaling complexes found in actin-mediated microvillar extensions of the photoreceptor cells (the rhabdomere). The eye also exhibits a light entrained-circadian rhythm, and we have recently observed that one component of this rhythm (BDBT) becomes undetectable by antibodies after exposure to light even though immunoblot analyses still detect it in the eye. BDBT is necessary for normal circadian rhythms, and in several circadian and visual mutants this eye-specific oscillation of detection is lost. Many phototransduction signaling proteins (e.g., Rhodopsin, TRP channels and Galpha also become undetectable shortly after light exposure, most likely due to a light induced compaction of the rhabdomeric microvilli. The circadian protein BDBT might be involved in light-induced changes in the rhabdomere, and if so this could indicate that circadian clocks contribute to the daily adaptations of the eye to light. Likewise, circadian oscillations of clock proteins are observed in photoreceptors of the mammalian eye and produce a circadian oscillation in the ERG. Disruption of circadian rhythms in the eyes of mammals causes neurodegeneration in the eye, demonstrating the importance of rhythms for normal eye function.